IMPLEMENTASI PEMBELAJARAN DARING DALAM MENGEMBANGKAN KARAKTER TANGGUNG JAWAB PESERTA DIDIK PADA PEMBELAJARAN EKONOMI DI SMA KEMALA BHAYANGKARI 1 KUBU RAYA - Pertiwi, Elsha; Sulistyarini, Sulistyarini; Okianna, Okianna (Universitas Tanjungpura, 2022)
AbstractThis study aims to determine the implementation of online learning in developing thecharacter of students' responsibility in economics subjects at SMAS KemalaBhayangkari 1 Kubu Raya. The research method used is a qualitative research methodwith a descriptive approach. The source of the data for this research is the economicsteacher of class XI IIS 1 and the data is the result of interviews with economics teachersand observation sheets and documentation. The results show that online learningplanning in developing the character of student responsibility made by the teacher forlearning in the form of lesson plans is very maximal and runs smoothly with apercentage of around 70%-80%, and a design for assessment is made, where theteacher plays a very important role in every learning implementation, and for theimplementation is going well for now. So online learning can develop the character ofstudents' responsibility in economic subjects at SMAS Kemala Bhayangkari 1 KubuRaya.Keywords: Online Learning, Student Responsibilities